2014
DOI: 10.1001/jamasurg.2013.3176
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preoperative 25-Hydroxyvitamin D Level and Hospital-Acquired Infections Following Roux-en-Y Gastric Bypass Surgery

Abstract: IMPORTANCE Postoperative hospital-acquired infections (HAIs) may result from disruption of natural barrier sites. Recent studies have linked vitamin D status and barrier site integrity. OBJECTIVE To investigate the association between preoperative vitamin D status and the risk for HAIs. DESIGN, SETTING, AND PARTICIPANTS A retrospective analysis was performed using propensity score methods to construct a matched-pairs cohort to reduce baseline differences between patients with 25-hydroxyvitamin D (25[OH]D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 46 publications
3
60
1
6
Order By: Relevance
“…In this study, we found that 25-hydroxyvitamin D positively correlated with CRP, TNFα and IL-6. There are several cross-sectional studies in literature that showed strong relation between 25-hydroxy vitamin D deficiency and sepsis or mortality (Quraishi et al 2014;Moromizato et al 2014). In contrast, the present study is the first study that was made in same groups before and after treatment and found high level of 25-hydroxyvitamin D in pre-treatment group.…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, we found that 25-hydroxyvitamin D positively correlated with CRP, TNFα and IL-6. There are several cross-sectional studies in literature that showed strong relation between 25-hydroxy vitamin D deficiency and sepsis or mortality (Quraishi et al 2014;Moromizato et al 2014). In contrast, the present study is the first study that was made in same groups before and after treatment and found high level of 25-hydroxyvitamin D in pre-treatment group.…”
Section: Discussioncontrasting
confidence: 56%
“…Vitamin D is thought to be involved in muscle function, cardiovascular disease, inflammation, immunity, insulin sensitivity, and cancer development. 1,2 Turan and colleagues inform us that more than a third of purportedly healthy adults, more than half of all hospitalized patients, and more than 95% of critically ill patients have vitamin D deficiency. This begs the question of whether low 25OHD levels are the result of disease, rather than a cause of disease.…”
Section: Commentmentioning
confidence: 99%
“…There have been several studies which have linked hypovitaminosis D to adverse post-surgical outcomes following a wide range of procedures [14]. Iglar and Hogan reviewed 31 studies linking hypovitaminosis D to complications such as increased risk of graft failure in renal patients [15], wound breakdown and infection [16,17], and organ transplant rejection [18,19]. In cases specific to orthopaedic practice, suboptimal vitamin D levels have been linked to refracture following surgical fixation of 5th metatarsal fractures [20], and there is evidence to support giving vitamin D supplementation to elderly patients with fractures of the hip [21,22] and proximal humerus [23].…”
Section: Discussionmentioning
confidence: 99%